Kinetic Simulation of Plasma in Ion Thruster Discharge Chamber. Comparison with Experimental Data. (2017) - Lovtsov, A.S.; Kravchenko, D.A.
Abstract: Development of electric propulsion systems (EPS) with high efficiency, reliability and long lifetime is required for solution of present-day space challenges. Ion thrusters (IT) are among the most promising types of EPS. This work is dedicated to numerical simulation of discharge chamber plasma. A 2D 3 V kinetic non-stationary particle-in-cell model has been developed. It includes several new techniques. Maintenance of quasi-neutrality at the cathode border allows the value of discharge current depending on the dynamic plasma parameters to be obtained. In addition, the model includes a technique for modelling operation of a power supply. It expects discharge current control by discharge voltage variation. Combination of these two features allows us to consider plasma discharge in the DC as a dynamic self-consistent system. Several simulations of IT-50 ion thruster operation modes were carried out using the present model. Simulation results and experimental data show sufficient agreement.